Climate-related uncertainties in urban exposure to sea level rise and storm surge flooding: a multi-temporal and multi-scenario analysis. (September 2019) - Ju, Yang; Lindbergh, Sarah; He, Yiyi; Radke, John D.
Abstract: Climate change-induced sea level rise and intensified storms pose emerging flood threats to global coastal urban areas. While such threats have been mapped, their uncertainties from different climate scenarios and longer planning horizons have yet to be addressed from both an exposure assessment and a stakeholder outreach perspective. Therefore, we chose the highly urbanized San Francisco Bay Area as an example to project its flood areas every 20 years between 2000 and 2100, under 24 varied climate scenarios with two greenhouse gas (GHG) concentration levels. We then assessed flood exposure by intersecting the flood areas with demographic and socioeconomic distributions, developed areas, lifeline infrastructures, and emergency responders in low elevation (<10 m) coastal zones. Our median estimates under the low GHG scenarios indicated that 10–38% of the items assessed above are flood-exposed in 2000–2020, with this exposure increasing to 20–54% during 2080–2100. The median estimates under the high GHG scenarios for the same periods are 0–35% and 40–67%, respectively. The expected uncertainties, or standard deviations, of the exposures for a given item assessed above under the low and high GHG scenarios are 1–2% in 2000–2020 and 7–10% in 2080–2100. Despite our modeling capability for a range of climate scenarios over the long term, some stakeholders, particularly those in the private sector, prefer near-term results with lower uncertainties. This implies the need for coastal urban areas to cope with climate-related uncertainties and to focus on the long term when developing strategies and policies for climate change adaptation. Highlights: We projected urban area's exposure to flood caused by sea level rise, intensified storms, and tide under a spectrum of climate scenarios and for five planning horizons between 2000 and 2100. We found increased exposure and greater uncertainties when the projection moved towards 2100, and that scenarios with stronger greenhouse gas concentrations were associated with greater uncertainties. While we were able to project flood under a range of climate scenarios and over the long term, some stakeholders preferred near-term and highly probabilistic results. Such preference implies the need for uncertainty-coping adaptation strategies and a long-term focus.